Ferrochelatase activity of plant frataxin - Armas, Alejandro Manuel (2019)
Frataxin plays a key role in cellular iron homeostasis of different organisms. It is engaged in several activities at the Fe–S cluster assembly machinery and it is also involved in heme biosynthesis. In plants, two genes encoding ferrochelatases (FC1 and FC2) catalyze the incorporation of iron into protoporphyrin IX in the last stage of heme synthesis in chloroplasts. Despite ferrochelatases are absent from other cell compartments, a remaining ferrochelatase activity has been observed in plant mitochondria. Here we analyze the possibility that frataxin acts as the iron donor to protoporphyrin IX for the synthesis of heme groups in plant mitochondria. Our findings show that frataxin catalyzes the formation of heme in vitro when it is incubated with iron and protoporphyrin IX. When frataxin is combined with AtNFS1 and AtISD11 the ferrochelatse activity is increased. These results suggest that frataxin could be the iron donor in the final step of heme synthesis in plant mitochondria, and constitutes an important advance in the elucidation of the mechanisms of heme synthesis in plants.